Sociocultural Factors Influencing Venture Creation among Purdah Women in Nigeria - Sikiru Issa Nuhu; Titus A. Umoru; Israel Segun Ogundele (Universitas Pendidikan Ganesha, 2026)
Venture creation among purdah women in Nigeria remains critically underexplored due to prevailing sociocultural constraints, particularly those rooted in societal norms and ethnic traditions. These women, while possessing entrepreneurial potential, often navigate rigid cultural expectations that hinder active participation in economic ventures. This study examines ‘Sociocultural Factors Influencing Venture Creation among Purdah Women in Nigeria’, with a view to promoting inclusive economic participation and social cohesion. The population was infinite. This is was used since there was no accurate statistical data of the respondents. A sample size of 400 respondents was determined using Taro Yamane’s (1967) formula for infinite population. Stratified random sampling was used to select sample for the quantitative aspect, while 40 purdah women were purposively selected for qualitative aspect. The study instrument achieved a reliability coefficient of 0.89 using Cronbach Alpha. Statistical analyses were conducted using mean, standard deviation, t-tests, and ANOVA. Findings revealed that societal norms exert a strong influence on venture creation (mean = 2.89, SD = 1.06), with traditional gender roles and community expectations often limiting women’s autonomy in business decisions. This implies that the society in which the purdah resides influences their venture creation decisions. They differ in responses as regards societal norms influence venture creation based on their qualifications (F6,350 = 508.818, P<0.05). Ethnicity, while exerting a lower overall influence (mean = 2.45, SD = 1.00), significantly varied across ethnic groups (F2,354 = 47.097, P<0.05), indicating that cultural interpretations of purdah differ across regions. The study concluded that entrenched social expectations and ethnic interpretations of purdah are key factors inhibiting venture creation among women. Purdah women with entrepreneurship knowledge will contribute immensely to economic development. It was recommended that community-based interventions be tailored to specific ethnic and cultural contexts, while advocacy and sensitization efforts challenge restrictive gender norms.